2018
DOI: 10.1097/md.0000000000013014
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent versus sequential whole brain radiotherapy and TKI in EGFR-mutated NSCLC patients with brain metastasis

Abstract: To examine the outcomes of concurrent versus sequential whole-brain radiotherapy (WBRT) and epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) in nonsmall cell lung cancer (NSCLC) patients with EGFR mutation.Retrospectively 105 patients with NSCLC, brain metastasis, and EGFR mutation (Affiliated Hospital of Guangdong Medical University, 01/2011 to 12/2014) were grouped as: EGFR-TKIs alone (n = 39, group A), EGFR-TKIs + concurrent radiotherapy (n = 34, group B), and radiotherapy followed by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Then we conducted the influence analysis of the included data ( Figures S1,S2), and founded out that Jiang et al, Ke et al and Magnuson (SRS) et al were the main origins which influenced the pooling outcome (26,29,32). The heterogeneity was effectively decreased or removed after exclusion of these three studies (I 2 =0.0%, P=0.680); Moreover, I 2 of iPFS was decreased to 38.5% (P=0.107) after removal of the three studies (byeon et al, Jiang et al and Chen et al) (23,26,27) which were considered as the culprit of heterogeneity by sensitivity analysis. The Egger's and Begg's test of included studies suggested no significant publication bias (P>0.05).…”
Section: Tki + Brain Rt Vs Tki Alone On Os and Ipfsmentioning
confidence: 97%
See 1 more Smart Citation
“…Then we conducted the influence analysis of the included data ( Figures S1,S2), and founded out that Jiang et al, Ke et al and Magnuson (SRS) et al were the main origins which influenced the pooling outcome (26,29,32). The heterogeneity was effectively decreased or removed after exclusion of these three studies (I 2 =0.0%, P=0.680); Moreover, I 2 of iPFS was decreased to 38.5% (P=0.107) after removal of the three studies (byeon et al, Jiang et al and Chen et al) (23,26,27) which were considered as the culprit of heterogeneity by sensitivity analysis. The Egger's and Begg's test of included studies suggested no significant publication bias (P>0.05).…”
Section: Tki + Brain Rt Vs Tki Alone On Os and Ipfsmentioning
confidence: 97%
“…Then, 9 papers were excluded by screening the type of article, including 2 comment, 3 case report, 1 letter and 3 conference abstracts. 16 candidates were fully reviewed and finally 12 papers meeting inclusive criteria and were selected for meta-analysis (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The flow diagram of our literature inclusion scheme was shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Many meta-analyses and retrospective studies regarding the combination of EGFR-TKIs with radiotherapy have yielded conflicting results. Some studies have reported the superior efficacy and survival benefit of upfront radiotherapy or radiotherapy plus EGFR-TKIs over EGFR-TKIs alone [18][19][20][21][22]. However, others have reported no survival benefit [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…WBRT can significantly reduce the intracranial progression rate and prolong the median iPFS and median OS; these results are consistent with those of previous studies. 22,24,25,29 Multivariate analysis showed that WBRT (P=0.016) is an independent prognostic factor in patients with multiple BM from NSCLC under EGFR-TKI targeted therapy. According to our study, a comprehensive treatment model of EGFR-TKI and WBRT in lung cancer patients with multiple BM can significantly prolong the survival of patients and further consolidate the position of WBRT in BM of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…22 Chen H and other studies have shown that simultaneous treatment of EGFR-TKI and WBRT improves patients' short-and longterm benefits compared with sequential or separate use. 29 Liu et al showed that in EGFR-mutant NSCLC patients with BM, the timing of brain RT has no effect on OS. 30 The optimal timing of brain RT for EGFR-TKI-treated lung cancer patients with BM is still inconclusive in clinical practice.…”
Section: Discussionmentioning
confidence: 99%